The Path to Expertise in Youth Sport: Using a Retrospective Interview in Three Different Competitive Contexts. Issue 2 (April 2014) - Diogo, Frederico; Gonçalves, Carlos Eduardo
The goal of this study was to identify contextual factors in the path to excellence in youth sport. 48 male athletes under 17 years of age ( M = 15.7 yr., SD = 1.0) from a soccer academy ( n = 20), a volleyball club ( n = 14), and an elite volleyball center ( n = 14) participated in the study. A standardized, retrospective interview was administered. Demographic information, training loads, and incidence of injuries were also collected. Male soccer players had more years of practice in sport than their male volleyball peers, but elite male volleyball players practiced more hours per week than the other athletes. The perception of intensity of training, physical effort, and concentration in male soccer players was higher than in male volleyball players. The high demands of expertise in professional soccer leads young athletes to begin training at early ages. The results showed that the environment specificity shapes the way young male athletes perceive their participation and commitment in sport.